Oblique wrinkling patterns on liquid crystal polymer core–shell cylinders under thermal load. (January 2021) - Zhao, Shichen; Xu, Fan; Fu, Chenbo; Huo, Yongzhong
Highlights: We have revealed tunable oblique wrinkling patterns in cylindrical core–shells under thermal load. We have developed a core–shell model accounting for director-induced anisotropic spontaneous strains. We have explored the effects of anisotropy of spontaneous strains on pattern formation and evolution. For general spatial director field, wrinkling patterns can be diamond-like, parallel bead-chain or oblique stripes. Director-affected phase diagrams on pattern selection are provided. Abstract: Smart soft materials, which can flexibly respond to external multi-physics stimuli, have attracted considerable attention over the past few years. Here, we present tunable wrinkling patterns in cylindrical core–shell systems under thermal load via the orientation of director in nematic liquid crystal polymer (LCP). To quantitatively analyze mechanical behavior and morphological evolution of LCP core–shell cylinders, we develop a core–shell model that accounts for director-induced anisotropic spontaneous strains. By tuning the alignment of liquid crystal director, we explore the effects of anisotropy of spontaneous strains on instability pattern formation and evolution. When the director is along the circumferential direction, wrinkling pattern can be axisymmetric or diamond-like, determined by a single dimensionless parameter C s which characterizes the stiffness ratio and curvature of the system. When the director is parallel to the axial direction, leading to circumferential expansion upon heating, the core–shell cylinder usually buckles into churro-like mode. For general spatial director alignment, the ultimate wrinkling patterns depending on the anisotropy state of spontaneous strains, can be diamond-like, parallel bead-chain or oblique stripe mode. We draw director-affected phase diagrams to provide an overall view of pattern selection affected by liquid crystal director orientation, which could be used to quantitatively guide the effective design of wrinkling morphology-related smart surfaces.